Physiological relevance of the neuronal isoform of inositol-1, 4, 5-trisphosphate 3-kinases in mice. (14th September 2020) - Blechner, Christine; Becker, Lore; Fuchs, Helmut; Rathkolb, Birgit; Prehn, Cornelia; Adler, Thure; Calzada-Wack, Julia; Garrett, Lillian; Gailus-Durner, Valerie; Morellini, Fabio; Conrad, Susanne; Hölter, Sabine M.; et al.
Highlights: ITPKA is mainly expressed in neurons of the central nervous system and is also overexpressed in tumor cells. In particular in lung cancer cells ITPKA exhibits oncogenic activities. Here a broad screen of itpka -deficient mice was performed to analyze the effect of ITPKA inhibition on normal cells. ITPKA is involved in the regulation of nociceptive pathways, sensorimotor gating and motor learning. Itpka -deficient mice exhibit a weak metabolic phenotype . These findings have to be taken into account when developing ITPKA inhibitors to block the oncogenic activity of ITPKA. Abstract: Inositol-1, 4, 5-trisphosphate 3-kinase-A (ITPKA) is the neuronal isoform of ITPKs and exhibits both actin bundling and InsP3 kinase activity. In addition to neurons, ITPKA is ectopically expressed in tumor cells, where its oncogenic activity increases tumor cell malignancy. In order to analyze the physiological relevance of ITPKA, here we performed a broad phenotypic screening of itpka deficient mice. Our data show that among the neurobehavioral tests analyzed, itpka deficient mice reacted faster to a hotplate, prepulse inhibition was impaired and the accelerating rotarod test showed decreased latency of itpka deficient mice to fall. These data indicate that ITPKA is involved in the regulation of nociceptive pathways, sensorimotor gating and motor learning. Analysis of extracerebral functions in control and itpka deficient mice revealed significantly reduced glucose, lactate, and triglyceride plasma concentrations in itpka deficient mice. Based on this finding, expression of ITPKA was analyzed in extracerebral tissues and the highest level was found in the small intestine. However, functional studies on CaCo-2 control and ITPKA depleted cells showed that glucose, as well as triglyceride uptake, were not significantly different between the cell lines. Altogether, these data show that ITPKA exhibits distinct functions in the central nervous system and reveal an involvement of ITPKA in energy metabolism.